Creating successful telementoring programs - Kochan, Frances K.; Pascarelli, Joseph T. (Perspectives in mentoring., 2005)
This volume, Technological Aspects of Mentoring, edited by Frances K. Kochan and Joseph T. Pascarelli, will examine mentoring in the technological age. It will focus upon the impact and use of technology in terms of program development, mentoring roles, problems and solutions and issues to be addressed including confidentiality, ethics, and implications for future practice. The editors will explore the possibilities for tomorrow from the work of today.